PARENTS 2 Study: a qualitative study of the views of healthcare professionals and stakeholders on parental engagement in the perinatal mortality review—from 'bottom of the pile' to joint learning. Issue 11 (2nd December 2018) - Bakhbakhi, Danya; Burden, Christy; Storey, Claire; Heazell, Alexander Edward; Lynch, Mary; Timlin, Laura; Gold, Katherine; Siassakos, Dimitrios
Abstract : Objective: Engaging bereaved parents in the review process that examines their care before and after a perinatal death might help parents deal with their grief more effectively and drive improvements in patient safety. The objective of this study is to explore whether healthcare professionals would accept or support parent engagement in the perinatal mortality review process. Design: Qualitative focus group interviews. Transcripts were analysed with an inductive thematic approach. Setting: Two geographically distinct tertiary maternity hospitals in the UK. Participants: Five focus groups were conducted with clinical staff including midwives, obstetricians, neonatologists, nursing staff and chaplaincy services. Results: Twenty-seven healthcare professionals unanimously agreed that parents' involvement in the perinatal mortality review process is useful and necessary. Six key themes emerged including: parental engagement; need for formal follow-up; critical structure of perinatal mortality review meeting; coordination and streamlining of care; advocacy for parents including role of the bereavement care lead; and requirement for training and support for staff to enable parental engagement. Conclusions: Healthcare professionals strongly advocated engaging bereaved parents in the perinatal mortality review: empowering parents to ask questions, providing feedback on care, helping generate lessons and providing them with the opportunity to discuss a summary of the review conclusions with their primary healthcare professional contact. The participants agreed it is time to move on from 'a group of doctors reviewing notes' to active learning and improvement together with parents, to enable better care and prevention of perinatal death.